Synthesis, spectroscopic and thermal characterization of Fe(III)-mixed ligand complexes and spectrophotometric determination of Fe(III) in various samples - Mohamed, Gehad Genidy; Hindy, Ahmed Mahmoud Mohamed; Rizk, Mahmoud Sabry; Sadek, Mai El-Sayed (European Journal of Chemistry, 2014)
The aim of the present study is to find a non time consuming, economical and reliable spectrophotometric procedures using commercially available spectrophotometric reagents for the determination of Fe(III) ions. The methods are based on the formation of colored ternary complexes using, 1,10-phenanthroline and eriochrome black T or tartrazine mixed reagents and improved using a cationic surfactant, cetyltrimethyl ammonium bromide. This surfactant interacts with the complex to build up true ternary complex. The most suitable conditions for determination of Fe(III) ions and the parameters affecting the reactions including pH, time, temperature, stoichiometric ratios and reagents concentrations are optimized. The effect of different interfering ions is studied together with the suitable masking agents. The developed methods are used for the determination of Fe(III) ions in the presence of cetyltrimethyl ammonium bromide in different types of water (polluted industrial waste, ground, river Nile and drinking water). The synthesis and spectroscopy studies of two Fe complexes were reported. Thermal analysis was carried out in order to give an idea about the thermal stability of the complexes.